Economic Development in Latin America Essay in Honor of Werner Baer - Esfahani, Hadi Salehi.; Esfahani, Hadi Salehi.; Facchini, Giovanni.; Facchini, Giovanni.; Hewings, Geoffrey J. D.; Hewings, Geoffrey J. D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
This book addresses a diverse set of challenges facing Latin American economies. These range from the role of neo-liberal policies, deficit targeting, import substitution, role of institutions, trade and regional development and human capital and poverty.